Pengaruh Motivasi Belajar dan Pemanfaatan E-Learning terhadap Prestasi Belajar Mahasiswa Jurusan Pendidikan Ekonomi - Widya Fraenka Sari; Tri Kurniawati (Jurnal Ecogen, 2020)
This study aims to: 1) analyze the effect of learning motivation on student achievement. 2) analyze the effect of e-learning utilization on student achievement. 3) To analyze the effect of learning motivation and e-learning utilization student achievement. Thie type of research is quantitative descriptive research. The population in this study are students of the Department of Economic Education, FE UNP in 2017-2018. The sample are 100 peoplestudent. The type of data in this study are secondary data and primary data. The data collection technique used is a questionnaire. The data that has been collected is analyzed by descriptive analysis. This research uses multiple regression analysis. The results of this study indicate that 1) learning motivation does not significantly influence student achievement. 2)utilization of e-learning has no significant effect on student achievement and 3) learning motivation and utilization of e-learning have no significant effect on learning achievement student achievement departement of economic education UNP.Keywords : motivation to learn, the use of elearning, the use of elearning